Transvaginal Drainage of Pelvic Abscesses and Collections Using Transabdominal Ultrasound Guidance - Kevin C. Ching; Jules H. Sumkin (Hindawi Limited, 2015)
Objectives. To evaluate clinical outcomes following transvaginal catheter placement using transabdominal ultrasound guidance for management of pelvic fluid collections. Methods. A retrospective review was performed for all patients who underwent transvaginal catheter drainage of pelvic fluid collections utilizing transabdominal ultrasound guidance between July 2008 and July 2013. 24 consecutive patients were identified and 24 catheters were placed. Results. The mean age of patients was 48.1 years (range = 27-76 y). 88% of collections were postoperative (n=21), 8% were from pelvic inflammatory disease (n=2), and 4% were idiopathic (n=1). Of the 24 patients, 83% of patients (n=20) had previously undergone a hysterectomy and 1 patient (4%) was pregnant at the time of drainage. The mean volume of initial drainage was 108 mL (range = 5 to 570). Catheters were left in place for an average of 4.3 days (range = 1-17 d). Microbial sampling was performed in all patients with 71% (n=17) returning a positive culture. All collections were successfully managed percutaneously. There were no technical complications. Conclusions. Transvaginal catheter drainage of pelvic fluid collections using transabdominal ultrasound guidance is a safe and clinically effective procedure. Appropriate percutaneous management can avoid the need for surgery.